THE ONTOLOGY OF FINANCIAL MARKETS, FUNCTIONS AND STRUCTURE EVOLUTION: THEORETICAL AND METHODOLOGICAL ASPECT - Nichkasova Yuliya; Bila Svіtlana (Scientific Journal of Pedagogy and Economics, 2019)
Search and formation of the optimal model of the financial market for stimulating the economic growth of the country is an actual problem of the current stage of development of Kazakhstan. The study of the dialectics of the development of capital as a factor of production made it possible to reveal the ontological nature of financial markets, which is based on systemic functional dualism. The article substantiates that the financial market, being an element of the economic system, forms the system dynamic core, which is based on the exchange of current purchasing power for future purchasing power. It is shown that economic development has stimulated the expansion of the functional apparatus of financial markets. Based on theoretical and methodological studies of their structure and character of modification, authors present grouping of functions of the modern financial market in the form of four functional clusters: ontological, dynamic, consulting, control and regulatory functions. The role of the financial sector in the resource provision of economic development is determined by the structural and functional characteristics of the financial system, which are formed under the influence of internal factors of a unique model of economic evolution, as well as external factors formed under the influence of the global economic processes. System analysis of the typology of financial markets allowed us to identify the most common types of their structure: with the dominant role of banks or the financial market. It is proved that this typology of the structure is rather conditional since banks are active participants in the financial market. For sustainable economic development, consistency of interaction between financial market institutions is important. Theoretical and methodological analysis of modern problems of financial markets functioning revealed the increasing amorphousness of the characteristic forms and properties of the financial market, the loss of specialization of financial instruments and the decisive role of globalization in this process. Initially, the unique specific ability of capital to dematerialize physically tangible productive assets is enhanced by its modern irrational characteristics, shaping the phenomenon of the domination of the financial market over the real economy. The prevalence abstractidealistic, irrational nature of the financial markets leads to the risks of loss of controllability. The article focuses on the growing role of state regulation of financial markets to ensure a balance of interests of its participants in the financial market, to ensure effective, sustainable and innovative economic development, as well as to reorient national and international investment flows to ensure the investment and innovation development of Kazakhstan.